Prospective Economic Evaluation Alongside the Telephone-Based Nurse-Delivered Interpersonal Psychotherapy for Postpartum Depression Trial - Hay, Susanne; Dennis, Cindy-Lee; Ravitz, Paula; Grigoriadis, Sophie; Maddalone, Elise; Dukhovny, Dmitry; Zupancic, John (American Journal of Perinatology, 2025)
In a previously reported, multi-site, randomized controlled trial in women with postpartum depression (PPD), telephone-based, nurse-delivered, interpersonal psychotherapy (IPT) compared with standard postpartum care showed a reduction of 24% in the incidence of PPD (Dennis et al, British Journal of Psychiatry, 2020). The economic implications of this therapy have not been explored. We aimed to determine the cost-effectiveness of telephone-based, nurse-delivered IPT compared with standard postpartum care, using resource utilization data collected alongside the clinical study.We conducted a prospectively planned economic evaluation using patient-level data from the IPT trial, which enrolled 241 mothers with PPD. We considered costs from a societal perspective, measuring direct medical costs from study logs and secondary sources, as well as evaluating costs borne by the mother and family (including both medical and non-medical expenditures) and wage losses through questionnaires. We used a time horizon of 12 weeks post-randomization, corresponding to the endpoint of the clinical trial. Costs are reported in (2022) Canadian dollars.Patients in the IPT group had more phone calls with public health nurses external to those provided by the study protocol (IPT 73% versus control 55%, p = 0.007) and fewer visits to psychiatrists (9% versus 22%, p = 0.008). However, there were no statistically significant differences in any of the cost categories or total societal expenditures (IPT group $6,653, control group $5,336, p = 0.234). When costs and effects were combined, the societal expenditure was $5,397 for each additional patient without PPD.Telephone-based, nurse-delivered IPT, as employed in this trial, showed no statistically significant differences in costs compared with standard care but resulted in improved clinical outcomes. Although associated with moderate uncertainty, the resulting incremental cost-effectiveness was well within the acceptable range for medical interventions in this population, and telephone-based, nurse-delivered IPT should be considered for patients with PPD.
Keywords: costs and cost analysis; depression; postpartum; interpersonal psychotherapy; healthcare delivery